Ilya Kabakov : Public Projects or The Spirit of a Place - Daghini, Giairo; Groys, Boris; Pietrantonio, Giacinto Di; Vettese, Angela; Fondazione Antonio Ratti, Como; Former Church of San Francesco, Como (Milano : Edizioni Charta Milano, 2001)
Bazel, Zaza ; Biscotti, Rossella ; Borzi, Maurizio ; Brotherus, Simo ; Cantor, Mircea ; Cheung, Amy ; Ekici, Nezaket ; Gruppo Mille (Roberta Iachini) ; Herskowitz, Daniel ; Hiah, Jeremy ; Iurlaro, Antonia ; Janig, Ursula ; Juhas, Daniel ; Kabakov, Ilya ; Lovsin, Polona ; Mueller, Tom Alexander ; Nicoletta, Sandrine ; Nzoko Yakobou, Tetang ; Odoni, Alessandra ; Patrnogic, Verica ; Rox, Rosy ; Ruscigno, Loredana ; Santorum, Michela ; Vanriette, Aude ; Veronesi, Lucia ; Zilberman, Ma'ayan
Ilya Kabakov : Public Projects or The Spirit of a Place, Advanced Course in Visual Arts, Fondazione Antonio Ratti, Como, 2000 / Former church of San Francisco, Como / Workshop, July 3-24, 2000 / Students' Exhibition, July 25 - September 10, 2000 / Public Installation by Ilya and Emilia Kabakov, The Fountain. Mother and son, July 2000 - June 2001
Engels
Italiaans
boek